Representasi Pribumi dalam Film Bumi Manusia (Kajian Semiotika Saussure) - Novi Rahmawati; Arif Ardy Wibowo; Rahina Nugrahani (Jurnal Ilmu Komputer dan Desain Komunikasi Visual, 2022)
Bumi Manusia is one of Hanung Bramantyo's films that managed to attract the attention of Indonesian audiences because apart from being based on a historical novel written by a famous writer, namely Pramoedya Ananta Toer, this film also tells about the life of the Indigenous people in the colonial era. This study aims to provide knowledge and understanding of Indigenous Representation using Saussure's Semiotic Analysis Model. The representation approach used is a constructionist approach used in the process through the language used. The method used in this study is qualitative with a descriptive approach, describing, explaining, and representing the object of research based on existing facts or evidence. The data analysis technique used is Saussure's semiotic approach with the concept, Signifier and Signified as well as Langue and Parole. The results of the analysis of this film represent that the natives are a nation that is useless, lazy, stupid, unprofitable, worthy of being slaves or servants, poor, weak, too old-fashioned or traditional, like dirty, smelly and pricey animals, deserves to be insulted, trampled on. -step on and throw it away like trash when it's no longer needed. The results of the analysis obtained that the natives is under an atrocity and must be stopped. In this film, the natives are humiliated, made slaves or treated arbitrarily in their own country by Europeans. The negative representation of indigenous peoples is a reflection for the target audience so that they can become more alert, productive and adaptive to new things so that the conditions experienced by indigenous people will not be repeated.